Adapting disability research methods and practices during the Covid-19 pandemic: Experiences from the field - Banks, Lena Morgon; Willan, Samantha; Inglis-Jassiem, Gakeemah; Dunkle, Kristin; Ganle, John; Shakespeare, Tom; Khan, Rifat Shahpar; Hameed, Shaffa; Machisa, Mercilene; Watson, Nicholas; Carpenter, Bradley; Smythe, Tracey; et al. (Institute of Development Studies, 2024)
This article was published in The IDS Bulletin [©2022 Rights managed by Institute of Development Studies] and the definite version is available at: https://doi.org/10.19088/1968-2022.130 The Article's website is at: https://bulletin.ids.ac.uk/index.php/idsbo/article/view/3172